Ectoparasite occurrence associated with males and females of wild rodents Oligoryzomys flavescens (Waterhouse) and Akodon azarae (Fischer) (Rodentia: Cricetidae: Sigmodontinae) in the Punta Lara Wetlands, Argentina - Lareschi, Marcela (2010)
The objective of this research was to study infestation parameters and indexes of ectoparasites associated with each sex of the wild rodents Oligoryzomys flavescens (Waterhouse) and Akodon azarae (Fischer) in the Punta Lara wetlands, Argentina. A trend towards higher mean abundance (MA) and ectoparasite specific richness was observed in males of O. flavescens whereas those values were similar for both A. azarae sexes. The prevalence of the following ectoparasites was significantly higher on males (P < 0.05): Mysolaelaps microspinosus Fonseca (65.2%) and Hoplopleura travassosi Werneck (73.9%) on O. flavescens, and Ixodes loricatus Neumann (71.4%) on A. azarae. Only H. travassosi mean abundance was significantly higher on males (MA = 44.1). Since I. loricatus and Hoplopleura spp. are involved in the transmission of pathogens that cause diseases in animals and humans, and whose reservoirs are rodent hosts, these results are epidemiologically important.